2009
DOI: 10.1097/acm.0b013e3181b6ba00
|View full text |Cite
|
Sign up to set email alerts
|

Interventions That Affect Gender Bias in Hiring: A Systematic Review

Abstract: Purpose To systematically review experimental evidence for interventions mitigating gender bias in employment. Unconscious endorsement of gender stereotypes can undermine academic medicine's commitment to gender equity. Method The authors performed electronic and hand searches for randomized controlled studies since 1973 of interventions that affect gender differences in evaluation of job applicants. Twenty-seven studies met all inclusion criteria. Interventions fell into three categories: application inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(131 citation statements)
references
References 58 publications
(197 reference statements)
3
123
0
2
Order By: Relevance
“…27 Our results also align with findings from a systematic review of interventions that mitigate gender bias in employment, which found bias against women being evaluated for positions that are traditionally or predominantly held by men. 28 This review identified strategies to mitigate this bias, including aiming for an applicant pool with at least 25% women, committing to the value of credentials before applicants are reviewed and training panel members in unconscious bias and the role that it can play in discussions and decisions. 28 A recent study found that a 20-minute workshop on implicit biases and strategies for overcoming them changed participants' perceptions of bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Our results also align with findings from a systematic review of interventions that mitigate gender bias in employment, which found bias against women being evaluated for positions that are traditionally or predominantly held by men. 28 This review identified strategies to mitigate this bias, including aiming for an applicant pool with at least 25% women, committing to the value of credentials before applicants are reviewed and training panel members in unconscious bias and the role that it can play in discussions and decisions. 28 A recent study found that a 20-minute workshop on implicit biases and strategies for overcoming them changed participants' perceptions of bias.…”
Section: Discussionmentioning
confidence: 99%
“…28 This review identified strategies to mitigate this bias, including aiming for an applicant pool with at least 25% women, committing to the value of credentials before applicants are reviewed and training panel members in unconscious bias and the role that it can play in discussions and decisions. 28 A recent study found that a 20-minute workshop on implicit biases and strategies for overcoming them changed participants' perceptions of bias. 29 Furthermore, a randomized trial involving faculty from 92 departments at 1 university showed an increase in self efficacy to engage in gender-equity-promoting behaviours after a 2.5-hour workshop 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our result suggests that perception of genderbased obstacles may affect working patterns of female physicians. Multiple strategies have been shown to mitigate gender bias in hiring (Isaac et al 2009) and there are effective interventions to correct gender-based career obstacles and help develop women's careers (Fried et al 1996;Benz et al 1998). Gender-based discrimination must be recognized as a major problem in Japanese medical field and urgent measures are needed to ensure equal opportunities in professional advancement for both male and female physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Resulting outcomes include unintentionally rating identically performing Black students as less academically capable than Whites, 8,9 and evaluating identically credentialed female applicants as less qualified than males. 10,11 Implicit bias develops early in life from repeated reinforcement of social stereotypes. Implicit pro-White bias occurs among children as young as 3 years old throughout the world.…”
Section: Origins Of Implicit Biasmentioning
confidence: 99%